COLOUR AS ONE OF THE BASIC SPHERES OF COGNITION - Bazarbaeva, Albina (Журнал иностранных языков и лингвистики, 2021)
The focus of this article is determined by the great interest of modern linguistics for the language world conceptualization research and a special emphasis to colour nomination study as the main marker of national cultures. The problems of discovering common and specific features in different linguistic world images are also important